Clinical-therapeutic considerations regarding the surgical treatment of acute arterial accidents - Goller, Wolfgang; Soto, Jose Pedro; Saccone, Rodolfo (Cirugía del Uruguay, 1974)
Reference to etiological factors which provoke acute arterial accidents: embolism, acute thrombosis, traumatisms and aneurismatic comp!ications is made. The therapeutic procedures for each case is summarized. The authors insist on intraoperatory arteriography as a complement of surgical therapy in each case. The importance of decompressive fasciotomy of ischemic Jimbs is pointed out, as well as the high frequency and treatment of associated deep venous thrombosis, which so often complicates the post-operative evolution. The authors insist that only irreversible ischemic lesion bounds reconstructive surgery, which is by no means limited just by a time term he indication of anticoagulants in post-operatory is summarized and the use and indication of fibrinolitics is pointed out.